2015
DOI: 10.1155/2015/358086
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 in Acute and Chronic Illness

Abstract: FGF23 is a bone-derived phosphaturic hormone that may become a useful biomarker for the identification of high-risk patients in chronic but also acute disease. It rises early in chronic kidney disease and is strongly and independently associated with excess morbidity and mortality. Emerging data suggest that FGF23 is also elevated in different scenarios of acute illness. In this review, we give an overview on the role of this interesting disease marker and potential and proven interventional strategies and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…Previous studies have already established a clear role for inflammation in the synthesis of FGF23 . In detail, inflammatory cytokines have been shown to induce FGF23 production , and some acute and chronic inflammatory diseases are associated with an elevated serum FGF23 level . Moreover, activation of NFκB itself enhances FGF23 generation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already established a clear role for inflammation in the synthesis of FGF23 . In detail, inflammatory cytokines have been shown to induce FGF23 production , and some acute and chronic inflammatory diseases are associated with an elevated serum FGF23 level . Moreover, activation of NFκB itself enhances FGF23 generation .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, FGF23 has gained attention as it has become clear that FGF23 may be a valuable and highly sensitive biomarker for different acute and chronic disorders . Patients with renal (acute kidney injury, chronic kidney disease), cardiovascular (coronary heart disease, myocardial infarction, atrial fibrillation), inflammatory, and metabolic diseases were found to have high levels of FGF23 . Inflammation implicated in most of the aforementioned diseases has been shown to be a major trigger of FGF23 formation .…”
Section: Introductionmentioning
confidence: 99%
“…Our patients received calcium supplements and vitamin D analogue (calcitriol) after PTX to keep serum calcium concentrations in the range of 7.0–8.0 mg/dL. It is worth noting that certain diets and medications can also modify FGF23 concentrations including a vegetarian diet, phosphate restriction or phosphate binders, vitamin D analogues, parathyroidectomy, cinacalcet, and kidney transplantation [16]. In parathyroidectomized rats, calcitriol significantly increased FGF23 levels [17].…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived phorbol esters are potent carcinogens that are effective through stimulating PKC activity [3]. Inflammation [4,5], renal and cardiovascular disease [6][7][8] are major triggers of the production of fibroblast growth factor 23 (FGF23), a proteohormone mainly produced in the bone [9] and implicated in the regulation of phosphate reabsorption and 1,25(OH) 2 D 3 (active vitamin D [10]) formation in the kidney [11]. The FGF23-mediated inhibition of renal phosphate transporter NapiIIa and CYP27B1, the key enzyme for the generation of 1,25(OH) 2 D 3 , is dependent on Klotho, a transmembrane protein [9].…”
Section: Introductionmentioning
confidence: 99%